Community-Based Interventions for People Affected by Leprosy: A Narrative Review - Masala, Clausewitz Welmatus; Haroen, Hartiah; Pramukti, Iqbal (Journal of Health and Nutrition Research, 2025)
This narrative review aims to explore community-based program interventions among patients with leprosy. This study employs the PCC (Population, Concept, Context) framework and collects data from six literature reviews accessed through the PubMed database. Keywords adjusted according to Medical Subject Headings (MeSH) terms ("Community-Based Program" OR "Community Intervention" OR "Community Health Program" OR "Community Engagement") AND ("Social Support" OR "Peer Support" OR "Community Support" OR "Psychosocial Support") AND ("Leprosy" OR "Hansen’s Disease"). Analysis of six articles, primarily from Asian and African contexts, reveals that community-based interventions are effective in reducing stigma, enhancing socio-economic participation, and strengthening leprosy detection and prevention strategies. These programs succeed through a multidimensional approach involving social support, education, and economic empowerment. The findings underscore that integrating psychosocial support and economic empowerment within community-led health initiatives is fundamental to achieving holistic and sustainable outcomes in leprosy care.